Accountability through Public Sector Accounting and the Quality of Financial Reports - Anggadini, S D; Santika, T; Agustin, R S P; Dwiparna, M B A; Damayanti, S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The primary objective was to investigate the impact of public sector accounting and the quality of financial reports on accountability in Indonesia, with a focus on the potential effects on sector performance in their respective fields. The study employed a descriptive and verification analysis method, utilizing a quantitative approach. A Random Sampling technique was used to select 257 respondents. The sampling was conducted randomly without regard to strata in the population. The primary data source for the study was obtained through questionnaires distributed to the respondents. To test the hypothesis, the study employed multiple linear regression analysis using the SPSS Version 26.0 software analysis tool. The results indicate that public sector accounting has a positive effect on accountability performance, and the quality of financial reports has a positive effect on accountability performance. These findings have significant implications for policymakers and stakeholders in the public sector, particularly in terms of strengthening accountability mechanisms and improving financial management practices. Moreover, this research has the potential to contribute significantly to the existing literature on public sector accounting and accountability in Indonesia. The study’s findings can serve as a valuable reference for future researchers seeking to explore similar topics and can aid in the development of more robust and comprehensive research frameworks. Ultimately, this research seeks to promote the overall development of the public sector in Indonesia and contribute to the country’s broader economic growth and prosperity.